INHERITANCE FOR EARLY MATURITY OF F1 HYBRID COMBINATIONS BASED ON AMERICAN AND MEXICAN COTTON VARIETIES IN KARKALPAKISTAN - Aytjanov Bakhytjan Uzakbaevich; Ramazanov Daniyar Bakhytbaevich; Aytjanov Uzakbay Yeshanovich (EPRA International Journal of Research and Development (IJRD), 2022)
Due to the short growing season in Karakalpakstan, high-yielding, intensive, optimally constructed new plants have not been created yet. In order to solve this problem, it is possible to change the negative correlation between fastness, fiber yield, length and productivity by supporting different hybridization methods from the US and Mexican cotton collection. In order to create high-yielding and high-quality varieties, based on the study of collection samples brought from the centers of origin of cotton, as well as from the USA and Mexico, they were involved in crossbreeding them with regionalized and promising new varieties in the conditions of Karakalpakstan. As a result, Ғ1 plants with an intensive and optimal structure were superior to their parents in almost all combinations of quick-growing traits, and the possibility of selecting quick-growing genotypes was created. It was found that the quickness sign is a polygenic sign and depends on the genotype of the sample participating in the crossbreeding.